The missing witness [large type] - Brennan, Allison (Brennan, Allison. Quinn & Costa thriller., 2024)
"When a key witness goes missing, Quinn & Costa must find her before a killer silences her for good... Detective Kara Quinn is back in Los Angeles to testify against a notorious human trafficker, finally moving past the case that upended her life. But when the accused is shot in broad daylight, the chaotic scene of the crime turns up few reliable bystanders. And one witness--a whistleblower who might be the key to everything--has disappeared. After another person close to the case is killed, it's clear that anyone who knows too much is in danger, and tracking down the witness becomes a matter of life-and-death. But as explosive secrets surface within the LAPD and FBI, Kara questions everything she thought she knew about the case, her colleagues and the life she left behind months ago. Now with FBI special agent Matt Costa's help, she must race to find the missing witness and get to the bottom of the avalanche of conspiracies that has rocked LA to its core...before it's too late"--